2020
DOI: 10.1177/1971400920977031
|View full text |Cite
|
Sign up to set email alerts
|

A pictorial review of brain arterial spin labelling artefacts and their potential remedies in clinical studies

Abstract: Arterial spin labelling is an emerging non-invasive magnetic resonance imaging technique for estimating the cerebral perfusion without the requirement for gadolinium-based intravenous contrast agents. Despite the wide range of applications in epilepsy, dementia, brain tumours, vascular malformations and stroke imaging, obtaining clinically useful arterial spin labelling data is technically challenging and prone to numerous artefacts. The objective of this review is to provide a comprehensive pictorial overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…14 Arterial spin labelling (ASL), which is a non-invasive MRI technique, may also be a good alternative; however, it has the drawback of having numerous artifacts. 15 In this case, the patient could remain at rest during distal flow blockage during the first angioplasty, but not during CAS. This phenomenon might be due to a decrease in collateral flow via the external carotid artery or leptomeningeal anastomosis, attenuated dilation of the cerebral artery, or a combination of both.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…14 Arterial spin labelling (ASL), which is a non-invasive MRI technique, may also be a good alternative; however, it has the drawback of having numerous artifacts. 15 In this case, the patient could remain at rest during distal flow blockage during the first angioplasty, but not during CAS. This phenomenon might be due to a decrease in collateral flow via the external carotid artery or leptomeningeal anastomosis, attenuated dilation of the cerebral artery, or a combination of both.…”
Section: Discussionmentioning
confidence: 87%
“…14 Arterial spin labelling (ASL), which is a non-invasive MRI technique, may also be a good alternative; however, it has the drawback of having numerous artifacts. 15…”
Section: Discussionmentioning
confidence: 99%
“…Recent pictorial review highlights the technical pitfalls in ASL, their diagnostic utility and imaging interpretations. 5…”
Section: Discussionmentioning
confidence: 99%
“…Considered as a reliable physiological marker of neuronal activity [11e13], ASL is a noninvasive fMRI technique which does not use a radioactive agent but rather arterial water as an endogenous tracer providing stable absolute quantification of regional cerebral blood flow (rCBF) [14]. ASL is quantitative, stable over time, and less variable across subjects [15], which makes it a specific, useful noninvasive method to measure rCBF in clinical studies [16]. Earlier research, applying covariance analytical approaches on structural anatomical brain data, has shown that baseline cortical morphological abnormality patterns between different regions of interest (ROIs) can increase clinical outcome prediction accuracy on an individual basis [17,18].…”
Section: Introductionmentioning
confidence: 99%